Implementasi Pemenuhan Kebutuhan Esteem (Penghargaan) Perspektif Abraham Maslow: Studi Kasus Di Sd N 1 Bantul Yogyakarta - Asriyadi; Muhammad Haqqin Nazily; Fika Fitriyana; Naisyheylla Zuhrotun Nissa; Nunuk Apriyani; Bagus Mahardika (Jurnal Ilmu Pendidikan, 2025)
This research explores the urgency of psychological aspects within the primary education environment through a comprehensive analysis of the implementation of esteem needs fulfillment among students at SD N 1 Bantul, Yogyakarta. Adopting Abraham Maslow's Hierarchy of Needs as the theoretical framework, this study aims to dissect how the need for self-esteem and recognition is integrated into daily pedagogical practices. The focus of the study is directed at three main pillars: identifying the various modalities of providing rewards implemented by educators, the significance of its impact on the escalation of learning motivation and the crystallization of students' self-concept, and mapping the determinant factors that serve as systemic supports or barriers in the implementation process. Methodologically, this research employs a qualitative design with a case study approach to gain a profound understanding of psychosocial phenomena within the school environment. Data were collected through triangulation techniques to ensure the validity of the findings, encompassing non-participatory observation of classroom dynamics, semi-structured interviews with key informants (teachers and students), and curatorial documentation studies related to students' achievement records and behavior. Informant selection was conducted using purposive sampling to ensure the representation of relevant and contextually rich data. All collected data were subsequently analyzed using the Miles and Huberman interactive model, which includes the phases of data reduction, data display, and conclusion drawing/verification. The results of the study are expected to provide a holistic overview that the fulfillment of esteem needs is not merely about giving praise, but is a strategic instrument in shaping students' mental resilience and positive character. The findings also identify challenges such as limited pedagogical understanding regarding reward variations and family environmental factors that influence the effectiveness of strengthening students' self-concept at school.